The Application of Storytelling: A Solution to Overcome the Students' Speaking Problem - Sitorus, Clara Resta Gihonita (JET (Journal of English Teaching), 2018)
AbstractThe main objective of this research is to improve the tenth graders’ speaking skill throughstorytelling technique at SMK Bhakti. This research is a two-cycle-process of classroom actionresearch. The subject of the research was the students of tenth graders at SMK Bhakti-2. Therewere 20 students (12 males and 8 females). The instruments were the test, observation, interview,and diary notes. The result indicated that there was significant improvement of students’ scoresin the Pre-test to Post-test II. The mean of students’ Pre-test scores was 48.20, and 63.30 forPost-test I. On the contrary, it was 77.70 in Post-test II. It was supported by interview, diarynotes, and observation showing that there was students’ interest in learning through theimplementation of storytelling. It, therefore, is suggested for English teachers to make use of thetechnique to actively encourage and increase the students’s positive learning attitude towardsspeaking English.Keywords: storytelling technique, action research, speaking skill